Interleukin‐6‐induced satellite cell proliferation is regulated by induction of the JAK2/STAT3 signalling pathway through cyclin D1 targeting. (21st July 2013) - Kurosaka, M.; Machida, S.
Abstract Objectives To determine whether interleukin‐6 (IL‐6) stimulates rat muscle satellite cell proliferation in culture, and if so, to clarify the signalling mechanisms. Materials and methods Primary satellite cells were isolated from thirty male F344 rats, 11 weeks of age. IL‐6 at concentrations of 0.01, 0.1, 1, 10 or 100 ng/ml was added to culture media. Results IL‐6 at 0.01–1 ng/ml induced dose‐dependent increase in cell proliferation. After treatment with 1 ng/ml IL‐6, cell proliferation increased by 31%, and p‐STAT3+/MyoD+ cells increased in number compared to those in control media (P < 0.05). Inhibitors of JAK2 (AG 490) and STAT3 (STAT3 peptide) blocked the increase in BrdUrd+ cell numbers at 6 h post stimulation with 1 ng/ml IL‐6 (P < 0.05). Furthermore, cyclin D1 mRNA expression and cyclin D1+/MyoD+ cell numbers significantly increased in cultures treated with 1 ng/ml IL‐6 compared to those in control media (P < 0.05). In contrast, treatment with 10 and 100 ng/ml IL‐6 did not stimulate cell proliferation. Treatment with 10 ng/ml IL‐6 induced greater SOCS3 mRNA expression than with 1 ng/ml IL‐6 and control media. Moreover, co‐localization of SOCS3 and myogenin was observed after treatment with 10 ng/ml IL‐6. Conclusions IL‐6 induced dose‐dependent increase in satellite cell proliferation by activating the JAK2/STAT3/cyclin D1 pathway.